The problem of distraction - North, Paul, 1971- (Stanford University Press, 2012)
We live in an age of distraction. Contemporary analyses of politics, culture and psychology insist on this. They often suggest remedies for it, yet fail to investigate the meaning and history of distraction itself. This book corrects this lack of distraction, defined not as the opposite of attention but as discontinuous intellect.